A parallel distributed processing model of stimulus-stimulus and stimulus-response compatibility. - Zhang, Huazhong; Zhang, Jun; Kornblum, Sylvan (Cognitive Psychology, 1999)
The writers present a parallel distributed processing (PDP) model of stimulus-stimulus and stimulus-response compatibility. They aim to advance previous research in bringing diverse cognitive and perceptual tasks together under a unified computational framework. They seek to integrate recent theoretical development in two different research areas; the dimensional overlap model in the study of compatibility and the PDP approach in computer modeling. They propose a PDP model of compatibility comprised of three-layered networks—input, intermediate, and output. They present a description of representational and processing assumptions of their model and of the model's simulation of major results, and they compare the model to other computational models of compatibility tasks.